PELUANG SERTA HAMBATAN PENGEMBANGAN USAHA/INDUSTRI KECIL DAN MENENGAH DI JAWA TENGAH - Shofia Nur Awami (MEDIAGRO, 2007)
Middle and small industry development in Central Java veryneeded in supporting economics. Seen potency had by Central Java like :demography, infrastructure, job generation/human resource, developedcompetent middle and small industry, more than anything else small andmiddle industry in agricultural sector. Because effort in agriculturalsector have some its, is more can stay at condition of economic crisis, canpermeate big labour relative, and its role in forming of domestic earningsof bruto. Active and effort support from central government and alsolocal government very expected in course of its. Problems of educatedunemployment also require be paid attention, considering college gradalso represent expected by human resource is its role in development.Keyword : Middle and small industry, Central Java, Labour force,Educated unemployment.